1991
DOI: 10.1109/72.80338
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent correlation associative memories

Abstract: A model for a class of high-capacity associative memories is presented. Since they are based on two-layer recurrent neural networks and their operations depend on the correlation measure, these associative memories are called recurrent correlation associative memories (RCAMs). The RCAMs are shown to be asymptotically stable in both synchronous and asynchronous (sequential) update modes as long as their weighting functions are continuous and monotone nondecreasing. In particular, a high-capacity RCAM named the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
114
0
4

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 12 publications
0
114
0
4
Order By: Relevance
“…Resumidamente, as pesquisas em memória associativa iniciaram na metade do século XX e receberam mais atenção nos anos 1980 após a publicação do famoso artigo de Hopfield [2,11]. Nos anos 1990, foram apresentados vários modelos que estendem a rede de Hopfield, por exemplo, a Memória Associativa de Capacidade Exponencial (ECAM) [4] e a Memória Associativa Bidirecional (BAM) [17]. Entretanto, tanto a rede de Hopfield como a ECAM e a BAM, são modelos usados para armazenar padrões binários.…”
Section: Introductionunclassified
“…Resumidamente, as pesquisas em memória associativa iniciaram na metade do século XX e receberam mais atenção nos anos 1980 após a publicação do famoso artigo de Hopfield [2,11]. Nos anos 1990, foram apresentados vários modelos que estendem a rede de Hopfield, por exemplo, a Memória Associativa de Capacidade Exponencial (ECAM) [4] e a Memória Associativa Bidirecional (BAM) [17]. Entretanto, tanto a rede de Hopfield como a ECAM e a BAM, são modelos usados para armazenar padrões binários.…”
Section: Introductionunclassified
“…Chiueh and Goodman had analyzed that the capacity of ECAM scales exponentially with N (the length of the stored vectors) in [8], and as its variants, we conjecture that DB-ECAM, DBS-ECAM, MECAM, DB-MECAM, and DBS-MECAM also possess comparable storage capacity to ECAM. But in fact, to prove this claim theoretically is difficult, if not impossible.…”
Section: Computer Simulationsmentioning
confidence: 99%
“…Chieuh and Goodman [8] have demonstrated that ECAM is asymptotically stable in both synchronous and asynchronous update modes by defining a Liapunov energy function. They have also shown that the asymptotic storage capacity of the ECAM scales exponentially with the length of memory patterns theoretically.…”
Section: Exponential Correlation Associative Memory and Modified Expomentioning
confidence: 99%
See 2 more Smart Citations